Study of high speed gas turbine in industry by fuel ratio and turbine speed - Mohamad Sufian, Khalid (2010)
The gas turbine is one of the power plant units which will produces electrical energy in high amount and continuously production. The gas turbine makes a great service namely in the past 40 years in the electrical power industry both with utilities and merchant plants as well as the petrochemical industry throughout the world. It is a system with compact low weight, and can use multiple fuel application such as a natural power plant for offshore platforms. Therefore, the purpose of the study for the high speed gas turbine is to determine the effect of turbine speed on the gas turbine operation. This study currently been done by using ET792 Two-Shaft Gas Turbine Demonstration Unit and which liquefied Petroleum Gas (LPG) used as a fuel. The experiment was performed by manipulating the gas generator speed and the gas turbine speed to determine the power output, the fuel consumption and the specific thrust output of the gas turbine. From the given result, gas turbine speed shown a great affects to the gas turbine performances. The power output and the reduced output thrust of the gas turbine increase when the gas turbine speed increase, but the fuel consumption decreasing when the gas turbine speed increases. The decreasing of the fuel consumption with the power output and the reduced output thrust increasing will reduce the overall operating cost. And also it will decrease the usage of fuel by the mean of the system.